Neurospora tetrasperma helper strains using the E gene - David D. Perkins (Fungal Genetics Reports, 1994)
In N. crassa, strains with an inactive mating type allele are available that can be used as one component of a forced heterokaryon, serving as a helper to shelter a second component that is infertile or otherwise disadvantaged because of some recessive trait (Griffiths and DeLange 1978 Genetics 88:239-254; Perkins 1984 Neurospora Newsl. 31:41-42). am1 ad-3B cyh-1 (FGSC 4564), which is heterokaryon- compatible with both A and a mating types in Oak Ridge background (het-C, -d, -e), has been especially useful. When such a phenotypically wild-type heterokaryon is used as one parent in a cross, the helper nuclei do not participate sexually and all progeny are parented by the disadvantaged component. Heterokaryons with the helper are also useful for stock preservation, assuring survival of genotypes that would otherwise be difficult to maintain.